Legal regulation of the household labor contract a comparative - Hussein, Zuber Mustaffa; Salih, Dlawer Mahmud (Journal of Legal and Political Studies, 2021)
This study deals with the domestic workers with regards to its concept, characteristics and elements, as well as the rights and obligations that the domestic worker and the home owner obligations, in addition to how it terminates, noting that the Iraqi legislator did not regulate this contract with special legislation, and excluded the category of domestic workers from the employment law’s essential part; such as determining and specifying working hours, rest times and vacations, which created a legal problem because its rules are scattered between more than one law, some of its provisions still exist under the labor laws in force, and for other provisions it is necessary to refer to the civil law. This study concludes with creating a set of conclusions and recommendations, including the recommendation for the legislator to enact special legislation to regulate the domestic work contract, and to clarify the most important rights and obligations of its parties, so that each one is fully aware of his/her rights and obligations, especially ensuring the rights of domestic service workers, the weaker party to a contract in the contractual relationship.
Keywords: domestic workers; Iraqi legislator; legal problem; employment law; contractual relationship